FORMATION OF ECOLOGICAL AWARENESS AND ENVIRONMENTAL CULTURE OF MEDICAL STUDENTS - Olena Snisar; Oleksandra Shevchenko (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The article considers the important problem of searching and introducing innovative forms and methods of ecological upbringing and environmental education in the educational process of the medical educational establishment. Medical workers first face the negative impact of environmental problems on human health, therefore formation of high level of their environmental awareness and culture, ability to apply knowledge of medical ecology while performing their professional duties is an important condition for their qualitative vocational training. The aim of the article is to analyze the benefits of creating an environmental squad in the medical educational establishment with a purpose to create a high level of the studets' environmental awareness, environmental culture and expositive behavior. The experience of the environmental squad Cherkasy medical academy to attract students to the ecological and elucidative and environmental protection, scientific research ecologically oriented. Effective methods and forms of environmental squad's work in spreading ecological knowledge are characterized, the main topics of scientific research work are presented. Stages of forming ecological awareness and ecological culture of future doctors have been analyzed, while working in the environmental squad, from expanding and systematization of ecological knowledge to the development of ecological style of thinking and environmentally safe behavior. The results of the study led to the conclusion that activity of such structure as an ecological squad in the medical educational establishment provides improved ecological upbringing and environmental education and allows training of medical specialists, who understand the danger of a complicated ecological situation for human health, will promote healthy lifestyle, help reduce the negative impact of harmful factors on the health of patients, as well as a conscious citizen, which is a patriot of his country, take proper care of its natural resources, carries out environmental activities.